2016
DOI: 10.18632/oncotarget.9752
|View full text |Cite
|
Sign up to set email alerts
|

Multi-kinase inhibitors interact with sildenafil and ERBB1/2/4 inhibitors to kill tumor cellsin vitroandin vivo

Abstract: We have recently demonstrated that multi-kinase inhibitors such as sorafenib and pazopanib can suppress the detection of chaperones by in situ immuno-fluorescence, which is further enhanced by phosphodiesterase 5 inhibitors. Sorafenib and pazopanib inhibited the HSP90 ATPase activity with IC50 values of ~1.0 μM and ~75 nM, respectively. Pazopanib docked in silico with two possible poses into the HSP90 ATP binding pocket. Pazopanib and sildenafil combined to reduce the total protein levels of HSP1H/p105 and c-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
(41 reference statements)
1
31
0
Order By: Relevance
“…Prior studies have demonstrated that pazopanib is an inhibitor of the chaperones HSP90 and HSP70 that was associated with a tertiary structural change in the NH2-termini of the proteins [7, 11]. Using vemurafenib resistant TPF-12-293 cells we re-confirmed that pazopanib could alter the structure of chaperones in melanoma cells as judged by reduced immuno-fluorescence at the NH2-termini but not at their COOH termini (Supplementary Figure 5).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Prior studies have demonstrated that pazopanib is an inhibitor of the chaperones HSP90 and HSP70 that was associated with a tertiary structural change in the NH2-termini of the proteins [7, 11]. Using vemurafenib resistant TPF-12-293 cells we re-confirmed that pazopanib could alter the structure of chaperones in melanoma cells as judged by reduced immuno-fluorescence at the NH2-termini but not at their COOH termini (Supplementary Figure 5).…”
Section: Resultssupporting
confidence: 63%
“…ATPase inhibition was associated with conformational changes in the ATP binding NH 2 -termini of the chaperone proteins and with the abilities of these chaperones to associate and co-localize with other chaperones and client proteins [7, 8]. It has also been reported that acetylation can also alter the activity of chaperones, generally thought to be an inhibitory effect, with the regulatory acetylation of HSP90 controlled by HDAC6 [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several prior publications we have shown that both the HDAC inhibitor sodium valproate (Depakote®) and the PDE5 inhibitor sildenafil (Viagra®) can enhance the formation of autophagosomes and autolysosomes caused by other agents, which in turn leads to elevated levels of tumor cell killing. [10][11][12] Thus, we next determined whether valproate or sildenafil could enhance "autophagy" and thus the lethality of [neratinib + palbociclib].…”
Section: Resultsmentioning
confidence: 99%
“…PDE5 is expressed in the wider vasculature and myocardium [11]. Tumor cells can over-express PDE5, as we have demonstrated in hepatoma, breast and NSCLC [7, 9]. PDE5 inhibitors have a well-established safety record and have been shown to be safe in combination with most other medications [12, 13].…”
Section: Introductionmentioning
confidence: 99%